Konflik peran ganda ibu rumah tangga yang bekerja: Sebuah kajian literatur - Agung Purwanto; Wa Ode Zusnita Muizu (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2023)
Dual-role conflict in married career women disrupts the continuity of home and office work, reducing performance at work and reducing family harmony. The purpose of this study is to examine the form of dual-role conflict experienced by working housewives with the demands of fulfilling the family economy and the strategies they use to overcome these conflicts. The research method used is systematic review research. The sources of data in this study are scientific articles, theses, theses and conference publications which have the topic of dual role conflict in women who work as government employees and teachers which were published in the last 10 years from 2013–2023. Data analysis using content analysis techniques. Based on this research, the forms of role conflict that often occur are conflicts based on time, tension, and behavior, and the resolution strategies carried out are time management, family management, and self-management.